Identifikasi Pertumbuhan Gulma Pada Penyiapan Media Tanam Tanah Gambut Setelah Pemberian Kapur Dolomit - Fahruddin Arfianto (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
The aim of this study is to know and identify how many weed seeds that can grow to the planting media and how much its growth on the planting media of peat soil after it was given prior by dolomite lime before it is used for cultivation of horticultural crops. This study was carried out for 4 (four) months in June-September 2015 in Experimental Garden of Muhammadiyah Palangkaraya University at Jalan Anggrek, Village of Kereng Bangkirai, District of Sabangau, the City of Palangka Raya, Central Kalimantan Province. The treatment factors were tested by using a completely randomized design with 9 replicates the form of dolomite lime (D) to the planting media peat soil that consists of 4 levels: D0 = 0 ton/ha; D1 = 3 tons/ha; D2 = 6 tons/ha; and D3 = 9 tons/ha. The observations were made on the number of weeds, the weight of wet weed that grows and the weight of dry weeds that grow during 14 days since the beginning of the incubation period of the planting media. The data were analyzed by using analysis of variance (F test) at the level of α = 0.05 and 0.01, and continued by using Fair Significant Difference Test at the 0.05 level.